Enhancing the clinical research workforce: a collaborative approach with human resources - Snyder, Denise C.; Gaudaur, Heather; Marchant, Mark; Viera, Laura; McCubbin, Andrea; Verble, William; Mendell, Angela; Gilliam, Christine (Frontiers in Pharmacology, 2024)
Jobs for clinical research professionals (CRPs) have grown increasingly complex over the past 20+ years. This is due largely to additional administrative burden for investigators, study teams, sponsors, Clinical Research Organizations (CROs), and sites, particularly Academic Medical Centers (AMCs). Furthermore, National Institutes of Health (NIH) has reduced capacity to effectively fund research recognizing this is dependent on the overall congressional budget, which creates greater pressure for clinician scientists to secure external support. It is widely known clinical research will continue to become increasingly more complex for clinician scientists. This manuscript explores adoption of a clinical research competencybased job classification framework from the Joint Task Force for Clinical Trial Competency (JTFCTC) (https://mrctcenter.org/clinical-trial-competency/) across several AMCs and the role of Human Resources (HR) in facilitating this process. This collaboration focuses on fostering successful projects tied to the business case in order to address equity and improve support for the clinical research enterprise.